Response of Islamist ond Holders of Sunda Wiwitan Against Wedding a Different Religion - Imam Sucipto; Yana Mulyana; Yudi Guntara (UIN Sunan Gunung Djati Bandung, 2020)
The purpose of this study was to determine the response of a pair of followers of Islam and Sundanese Wiwitan to interfaith marriages in Cigugur. This research uses descriptive analysis method with a qualitative approach. Whereas the framework for thinking uses the grand theory of Joachim Wach, middle of the Ninian Smart theory and the applicative theory of phenomenology of Edmund Husserl. The results showed that the response of interfaith marriages was as follows: Interfaith marriages were a hidden truth, Embodiments of compassion, differences were a necessity, human rights, feelings of tumarima, strong mentality, and not recognition but understanding.